Diffusion tensor imaging of the brain white matter microstructure in patients with chronic kidney disease and its correlation with cognition - Zhang, Chaoyang; Yu, Huan; Cai, Yan; Wu, Ning; Liang, Shuang; Zhang, Chun; Duan, Zhiyu; Zhang, Zhou; Cai, Guangyan (Frontiers in Neurology, 2022)
Purpose: In individuals with chronic kidney disease (CKD), neurological damage is commonly observed. This neurodegeneration is closely linked to microstructural damage to the brain white matter due to the high incidence of cognitive dysfunction. However, the specific pathogenesis of CKD nephropathy caused by cognitive system developmental disorders remains unclear. This study aimed to examine the correlation between cognitive impairment and diffusion parameters obtained on diffusion tensor imaging (DTI) of abnormal white matter tracts in CKD patients. Methods: Sixty-four patients with CKD were divided into the non-dialysis-dependent CKD (NDD-CKD) group (n=26) and dialysis-dependent CKD (DD-CKD) group (n=38) according to the estimated glomerular filtration rate, whereas 43 healthy control subjects (normal control [NC]) were included and underwent cranial magnetic resonance imaging during the same period. Differences in the abnormal white matter microstructure and correlations between them and cognitive scores were assessed using several parameters between the groups. Results: There were more extensive peri-lesions and distant white matter microstructural changes in the DD-CKD and NDD-CKD groups than in the NC group. DTI diffusion parameters in abnormal white matter regions were associated with impaired cognitive function in CKD patients. The DD-CKD group had worse cognitive function and more severe microstructural damage in the cerebral white matter than the NDD-CKD group. Conclusion: CKD patients showed cognitive impairment and changes in the brain white matter microstructure; CKD can lead to extensive white matter tract damage. Additionally, diffusion parameters can be used as a complement to describe structural brain damage in CKD patients.